Perception and Practices of ICT Integration in Higher Education Classroom - Mishra, Nirmal Raj (Rupantaran: A Multidisciplinary Journal, 2021)
ICT integration in pedagogy has created the new discourse in our educational institutions. It has created the teaching learning is more challenging as well as productive. Gaining these insights, this study searched the perception and practices of ICT integration in higher education classroom and its integrating ways in teaching. This study used the qualitative research design whereas applied the phenomenological design to inquiry. For study, I selected the study area and informants through the convenient and purposive sampling respectively. The focus group discussion, in-depth interview and personal introspection helped me to understand the phenomena of ICT. The major finding is that the motivation factor is crucial for integration of ICT tools. The finding showed that ICT tools can integrate in six phases such as motivation, infrastructure development, training, bridge up, implementation, and monitoring. The ICT tools can be integrated through the brainstorming, self-presenting, collaborative, problem-based learning and project-based learning techniques/methods. The successful integration requires the support and training for the teachers and students. It always promotes the learning culture in supportive way and creates the opportunities to access in information to the users.